2013
DOI: 10.1038/ajg.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Success of GUT-Directed Group Hypnosis for Patients With Refractory Irritable Bowel Syndrome: A Randomized Controlled Trial

Abstract: GHT improves IBS-related QOL, is superior to SMT alone, and shows a long-term effect even in refractory IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 34 publications
4
108
0
4
Order By: Relevance
“…30 Results are in accordance with adult IBS trials showing that HT is superior to a variety of control treatments, with long-lasting effects. [63][64][65][66] Working mechanisms of HT are still poorly understood, but outcomes of adult studies hypothesize that HT affects both physiologic processes, such as colonic motility and pain-processing brain regions, and psychological factors, such as stress and dysfunctional cognitions. [67][68][69] CBT aims to change attitudes, cognitions, and behavior that may play a role in generating or maintaining symptoms and is effective in improving pain and other IBS symptoms in adults.…”
Section: Alternative Medicinementioning
confidence: 99%
“…30 Results are in accordance with adult IBS trials showing that HT is superior to a variety of control treatments, with long-lasting effects. [63][64][65][66] Working mechanisms of HT are still poorly understood, but outcomes of adult studies hypothesize that HT affects both physiologic processes, such as colonic motility and pain-processing brain regions, and psychological factors, such as stress and dysfunctional cognitions. [67][68][69] CBT aims to change attitudes, cognitions, and behavior that may play a role in generating or maintaining symptoms and is effective in improving pain and other IBS symptoms in adults.…”
Section: Alternative Medicinementioning
confidence: 99%
“…Validierungsstudien bezüglich der Rom I-III Kriterien sind nur spärlich vorhanden [8]; eine kürzlich publizierte Arbeit zeigte eine Sensitivität der aktuell gebräuchlichen Rom III Kriterien (Tabelle 1) für die Diagnose eines RDS durch Allgemeinpraktiker von 75% [11]. [27]. Im Gegensatz dazu hat sich die Akupunktur in mehreren…”
Section: Bis Zu 25% Aller Ambulanten Gastroenterologischen Patienten unclassified
“…As we were conducting our meta-analysis, advance online publication of this study was reported in February 2013, so we have included it in our review. 24 Agreement between authors for trial eligibility was substantial (k statistic = 0.79).…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…1). 11,[20][21][22][23][24] One study reported 2 RCTs being conducted on different settings in one publication. 20 One of the studies that we initially excluded was published only in abstract form.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%